2014
DOI: 10.3928/01484834-20140922-03
|View full text |Cite
|
Sign up to set email alerts
|

Association of Faculty Perceptions of Work–Life With Emotional Exhaustion and Intent to Leave Academic Nursing: Report on a National Survey of Nurse Faculty

Abstract: The current and projected nurse faculty shortage threatens the capacity to educate sufficient numbers of nurses for meeting demand. As part of an initiative to foster strategies for expanding educational capacity, a survey of a nationally representative sample of 3,120 full-time nurse faculty members in 269 schools and programs that offered at least one prelicensure degree program was conducted. Nearly 4 of 10 participants reported high levels of emotional exhaustion, and one third expressed an intent to leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
121
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(130 citation statements)
references
References 18 publications
8
121
1
Order By: Relevance
“…Perceived unreasonable workloads including high student numbers and insufficient support led to job dissatisfaction and greater chances of experiencing burnout (Sarmiento et al, ). This finding echoes Yedidia et al, () who identified dissatisfaction with workload issues was a major factor that contributed to burnout. Within the Australian context, McAllister et al () identified role overload, isolation, a nonvalidating culture, pace of change, and work role pressures as a challenge in meeting the needs of nursing academics.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Perceived unreasonable workloads including high student numbers and insufficient support led to job dissatisfaction and greater chances of experiencing burnout (Sarmiento et al, ). This finding echoes Yedidia et al, () who identified dissatisfaction with workload issues was a major factor that contributed to burnout. Within the Australian context, McAllister et al () identified role overload, isolation, a nonvalidating culture, pace of change, and work role pressures as a challenge in meeting the needs of nursing academics.…”
Section: Resultssupporting
confidence: 84%
“…Yedidia et al () found that the major contributors to burnout were dissatisfaction with increasing workloads and perceived inflexibility with balancing work and family life. Their study surveyed n = 3,120 full‐time nurse faculty members from 269 schools offering a degree programme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that as WL increases, satisfaction and intent to remain in the academe decreases. This is congruent with findings related to WL (Ryan, 2012;Enders et al, 2015;Yedidia et al, 2014), especially accounts detailing the long work hours (e.g., Kaufman, 2007;Lindfeld et al, 2015) and work that is performed outside of the confines of the academic organization (Bentley & Kyvik, 2012;Dennison, 2012;Kuntz, 2012). Although not statistically significant in our model, it is interesting to note that WL was a positive predictor of PPE, suggesting that faculties in these academic organizations perceive higher WL as positively predicting performance evaluations.…”
Section: Discussionsupporting
confidence: 90%
“…Extant research shows that balance between work and personal life is important among nursing faculty (Tourangeau et al, 2014), and lack of balance can lead to dissatisfaction with work, and a perceived inability to achieve a work-life balance among nursing faculty (Yedidia et al, 2014). Interestingly, Lindfelt et al (2015) found that members of the pharmacy school faculty reported a satisfaction with their position within their organization but were simultaneously dissatisfied with their work-life balance due to perceived overly long workweeks and lack of sleep.…”
Section: Introductionmentioning
confidence: 99%